O jovem e o mercado de trabalho : uma análise da inserção através do Programa Jovem Aprendiz implementado pelo SENAC em Sorriso/MT - Retiz, Marcia Helena Milesi (2014)
The present study aims to analyze the insertion of the young into the labour market through the program young apprentice implemented by SENAC in Smile/MT. This program is a Federal Government initiative, regulated and evaluated by the Ministry of Labour and is aimed at training and professional qualification of young people with a view to integration into the labour market. This program is materialized by law number 10.097/2000 that along with the Decree nº 5.598/2000 establishes a public/private partnership for young people between 14 to 24 years to be absorbed by the companies through a learning contract. Thus, the theoretical discussion part of Central categories, youth, professional education and work. The methodological procedures adopted for this study were the bibliographic survey and semi-structured interviews and documentary. The subjects of the research were teenagers graduating apprentices, those responsible for the selection process and recruitment of young apprentices in firms and the Coordinator of the SENAC, institution responsible for qualification of young apprentices in the municipality of Smile/MT. The data collected through this study demonstrated that despite the public policy embodied in the program young apprentice being able to insert many young people in the labour market, does not guarantee the permanence of the same employment since they were found limitations ranging from the formulation of this policy until the question of the commitment of companies to adhere and develop the program. Thus, the issue is more complex than the simple fact of inserting young into the labour market.